Icaritin Attenuates HSC Activation by Down-regulating the HIF-1α and TGF-β/Smad Signaling Pathways to Ameliorate Liver Fibrosis - Feng, Keping; Fei, Qiaoman; Huang, Na; Du, Ke; Zhang, Chengbo; Fan, Yudan; Zhou, Ying; Zhao, Yaping; Liu, Pengfei; Li, Zongfang (Current Medicinal Chemistry, 2025)
<span class=
Keywords: hepatic stellate cell (HSC) activation